PENERAPAN PEMBELAJARAN AKTIF KREATIF EFEKTIF DAN MENYENANGKAN (PAKEM) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA SISWA KELAS VII MATA PELAJARAN PAI SMP AL HUDA JATI AGUNG - Tuti Alawiyah (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
The learning achievements achieved by students are influenced by various factors, including student intelligence, learning motivation, teacher professionalism, student health, infrastructure, parents' economy, environment, quality of learning, etc. The quality of learning is an important factor in increasing student learning achievement. "The more conducive the learning environment of a school, the greater the possibility of learning achievement achieved by children. The population in this study was 34 class The aim of this research is to improve the quality of learning of Islamic Religious Education teachers at SMP Al Huda Jati Agung, improve student learning achievement in the field of Islamic Religious Education at SMP Al Huda Jati Agung and to find out whether Creative Active Learning is Effective and Fun (PAKEM) can Improve Learning Achievement Students of PAI Subjects SMP Al Huda Jati Agung Based on the research results and data analysis of this thesis research, it can be concluded as follows: Active Creative Effective and Fun Learning (PAKEM) can improve learning achievement in PAI Subjects SMP Al Huda Jati Agung. Quality of Active Creative Effective and Fun Learning (PAKEM) teacher SMP Al Huda Jati Agung achieved a score of 85 with a good mark